Teaching simultaneous interpreting: The early stage - Alexandra G. Anisimova; Anastasiya E. Fedotova; Inna N. Fomina (Peoples' Friendship University of Russia (RUDN University), 2021)
The article deals with the initial stage of training simultaneous interpreters and developing their professional skills. The authors single out and analyse a number of abilities and skills that learners are expected to develop in order to successfully obtain the qualification of simultaneous interpreters and offer a system of exercises and tasks that is intended to assist their acquisition. The article tackles the following issues typically arising at the early stages of student training: inability of unprepared students to concentrate and keep a lasting focus on the meaning and the structure of the source speech utterance, inability to control their short-term memory, the unfamiliar situation where the student is required to listen and speak at one and the same time, a lack of control over intonation and structure of his or her own speech during the interpreting process. In terms of language, particular attention is paid to the crucial role of collocations and fixed expressions in teaching simultaneous interpreting, as well as processing information that requires precision. The study is based on a textbook on political, economic, and legal translation which has been successfully used during several years at the Department of Theory and Practice of Translation at Lomonosov Moscow State University as a key training input. The methods of the current research include contextual and comparative analysis, information synthesis as well as experimental student training. The latter showed that learners' performance substantially improved, both immediately after some of the preparatory exercises (particularly those aimed at short-term memory and anticipation skills development) and in the long run. The authors believe that exercises described here can form a sound basis for developing skills necessary for simultaneous interpreters.